How do we build a picture of a patient in prolonged disorder of consciousness?. Issue 10 (25th November 2020) - Wilford, Susie; Howard, Alice
ABSTRACT: Accurate diagnosis of prolonged disorders of consciousness can be challenging and requires the input of a specialist interdisciplinary team who are experienced in informal assessment as well as the administration of formal validated observational assessment tools. There is limited guidance on the selection of these assessment tools. This study examines the factors involved in a team's choice making and how choice of assessment helps build a picture of a patient. Twelve clinicians working within a specialist prolonged disorders of consciousness unit participated in the study. Five took part in an individual structured interview and seven took part in a focus group. Data were evaluated using thematic analysis. The results show that there was a range of factors which influenced decisions over choice of assessment tools. No one assessment tool is perfect and therefore participants favour combining the characteristics of two assessment tools in order to achieve a higher-quality assessment. The use of two assessment tools rather than one, is thought to be key in helping to build an overall picture of the patient. The findings of this study may be useful in the training of clinicians working with this specialist caseload, in the future development of tools themselves and in guiding further research into using a combination of assessment tools for best outcome in this patient group.